Socioeconomic inequality in overweight/obesity among US children: NHANES 2001 to 2018 - Traore, Stanislav Seydou; Bo, Yacong; Kou, Guangning; Lyu, Quanjun (Frontiers in Pediatrics, 2023)
Background: Previous research has found that the prevalence of childhood overweight/obesity varies depending on household income, ethnicity, and sex. The goal of our research is to examine changes over time in socioeconomic inequality and the prevalence of overweight / obesity among American children under five by sex and ethnicity. Methods: This cross-sectional analysis used data from the National Health and Nutrition Examination Surveys (NHANES) collected from 2001-02 to 2017-18. Overweight /obesity in children under five (Body Mass Index (BMI)-for-age z-score > 2 standard deviations) was defined according to the World Health Organization (WHO) growth reference standard. The slope inequality index (SII) and the concentration index (CIX) were used to measure the socioeconomic inequality in overweight/obesity. Results: Between 2001–02 and 2011–12, childhood overweight/obesity in the United States decreased from 7.3 to 6.3%, and had increased to 8.1% by 2017-18. However, this pattern varied widely by ethnicity and sex. For both the 2015-16 and 2017-18 surveys, overweight/obesity was more concentrated in the poorest household quintile for overall Caucasian children ((SII= -11.83, IC 95%=-23.17, -0.49 and CIX=-7.368, IC 95%=-13.92, -0.82) and (SII= -11.52, IC 95%=-22.13, -0.91 and CIX=-7.24, IC 95%=-13.27, -1.21), respectively ) and for males of other ethnicities ((SII= -13.93326, IC 95%=-26.95, -0.92) and CIX=-8.553042, IC 95%=-0.86, -16.25) and (SII= -21.19278, IC 95%=-40.65, -1.74) and CIX=-13.11, IC 95%=-1.42, -24.80), respectively). In the last three surveys, overweight/obesity was also more concentrated in the poorest household quintile for the overall children of other ethnicities. With the exception of African American females in the 2013-14 survey, for whom overweight/obesity was significantly concentrated in a quintile of the richest households (SII= 12.60, 95% CI=0.24, 24.97 and CIX= 7.86, 95% CI=15.59, 0.12); overweight/obesity was found to be concentrated in the richest household quintile for overall African American children, but not significantly so. Conclusions: Our findings give an update and reinforce the notion that overweight/obesity in children under the age of five has increased and that related wealth inequalities are a public health problem in the United States.